ANALISIS POTENSI PENGEMBANGAN PERTANIAN ORGANIK DAN KONVENSIONAL DI KECAMATAN BAITO DALAM MENDUKUNG MISI KETAHANAN PANGAN BERKELANJUTAN KABUPATEN KONAWE SELATAN - Hariyanto Liambo; Sahta Ginting; La Ode Afa (Jurnal Perencanaan Wilayah, 2020)
The purpose of this study was to determine: 1) Potential development of organic and conventional agriculture in terms of land area and the potential availability of land in the future will come in Baito District; 2) The feasibility of organic and conventional farming in the Baito District in order to ensure business continuity and benefits; and 3) Directions for the development of organic and conventional agriculture in Baito District to support sustainable food security missions in Konawe Selatan District. Research is a quantitative study. The number of samples was 149 farmers. Data analysis was performed with a spatial approach (GIG ArcView) and qualitative descriptive. The results of the study concluded that; 1) The agricultural potential in Baito District in terms of the area cultivated by farmers is 1,363 ha consisting of organic farming around 626.63 ha and conventional 736.37 ha, and supported by the availability of land for future agricultural development in accordance with the spatial plan until 2033 namely 3,349.67 ha; 2) Organic farming business undertaken by the community in Baito District consists of thirteen (13) commodities namely; field rice, corn, peanuts, cassava, soybeans, cayenne peppers, eggplants, chayote, spinach, spinach, pineapple, papaya and bananas all of these types are feasible to be developed because they have an R / C value> 1. Whereas conventional farming businesses that cultivated consists of seven (7) commodities namely; lowland rice, soybeans, large chillies, spinach, apple tomatoes, cucumbers and beans all of these types are suitable to be developed because they have an R / C value> 1; and 3) Directions for the development of organic and conventional agriculture in Baito District to support the mission of sustainable food security in South Konawe Regency are; (a) it is necessary to correct the development of organic agriculture and initiate the formation of a pilot project area; (b) Development of organic and conventional agriculture with a planning approach (political, technocratic, top-down and bottom-up and participatory); and (c) the regional concept approach, namely conventional agricultural areas in Wonua Raya Village, Mekar Jaya Village and Baito Village (964.32 ha); the central area of organic agriculture development in Matabubu Village, Amasara Village, Ahuangguluri Village and Sambahule Village (1,965.10 ha); and supporting areas in Tolihe Village, Wanua Raya Village and Mekar Jaya Village.